Hubungan antara Kualitas Tidur dan Tekanan Darah Lansia - Jannah, Raudatul; Riskawati, Heni Marlina; Salfarina, Anna Layla (Jurnal Gema Keperawatan, 2023)
The process of declining health in elderly people results in reduced effectiveness of sleep time, so that adequate sleep quality is difficult to achieve, causing various sleep problems to arise. When someone experiences sleep disturbances, their blood pressure will increase, putting them at risk of developing hypertension. The aim of this research is to determine the relationship between sleep quality and blood pressure in the elderly at Posbindu Mambalan, Mambalan Village, Gunung Sari District. This research is a type of quantitative research witha cross sectional approach. The sample in this study was all elderly people who actively participated in Posbindu activities in Mambalan Village, totaling 27 elderly people. The sampling technique used was total sampling. The instrumentsin this study used PSQI (Pittsburgh Sleep Quality Index) and aneroid blood pressure monitor and stethoscope. Data analysis uses the Chi-Square Test. The results of the study showed that the majority of elderly people had poor sleep quality, 20 elderly people (74.1%), blood pressure with grade 1 hypertension, 10 elderly people (40.7%). Bivariate analysis showed a p-value of 0.013 0.05, which means there is a significant relationship between sleep quality and blood pressure in the elderly. The conclusion in this study is that there is a relationship between sleep quality and increased blood pressure in the elderly, the worse the sleep quality, the higher the risk of increasing blood pressure. It is hoped that seniors can improve their sleep quality by maintaining their eating and drinking patterns and scheduling their sleeping hours.